Real-world management, resource use, patient-reported outcomes and adherence in patients receiving direct oral anticoagulants for first stroke attributed to non-valvular atrial fibrillation in secondary care: A UK mixed-methods observational study - James Uprichard; Liqun Zhang; Anand Dixit; Yaqoob Bhat; Amit Mistri; Dipankar Dutta; Khalid Rashed; Dumin Karunatilake; Chris Hatton; Joe Eva; Amelia Reed (PLoS ONE, 2025)
This real-world study investigated the patient-related factors, characteristics, and outcomes of adult patients with non-valvular atrial fibrillation (NVAF) receiving a direct oral anticoagulant (DOAC) for secondary stroke prevention. This was a multi-centre, mixed-methods, non-interventional study conducted in 8 UK secondary care National Health Service centres. The study included adult patients who presented with first ischaemic stroke associated with NVAF without previous anticoagulants. Group 1 included all patients. Group 2 is comprised of prospectively enrolled patients who were initiated on apixaban (n = 49), edoxaban (n = 39) or rivaroxaban (n = 5) post-first stroke from Group 1. The primary objective (Group 1) was to describe patients’ demographics, clinical characteristics, and medical history, stratified by the anticoagulant prescribed. The secondary objectives (Group 2) were to describe the patient management pathways, hospital resource use and clinical assessments associated with DOAC treatment, and the patient-reported satisfaction and experience of DOAC treatment. 234 patients were recruited from 8 centres (Group 1). Baseline CHA2DS2-VASc risk scores ranged from 2–7; 70% (157/224) had a score of ≥4. 86% (n = 202/234) of patients presented with stroke at accident and emergency. For Group 2, the median time from stroke to first DOAC dose was 6 (IQR, 2.0–10.2; n = 88) days; 50% patients had ≥ 1 outpatient visit recorded related to AF or DOACs. At 3 and 6 months, 73% (46/63) and 83% (43/52) had high (score of 8) Morisky Medication Adherence Scale score (MMAS-8), respectively. No patients reported being dissatisfied at 3 or 6 months post-DOAC initiation. The study findings demonstrate high levels of adherence, persistence, and treatment satisfaction in the 6 months post-initiation of DOAC after first stroke attributable to NVAF in patients. The presented results provide clinicians with valuable insights into the experience of post-stroke patients with NVAF receiving treatment with a DOAC for secondary prevention of stroke during the 6 months post-stroke.